Phagocytic activity in people recovering from Corona Virus infection (Texas Journal of Agriculture and Biological Sciences, 2022)
The study aimed to measure the phagocytic activity of people recovering from Covid 19 after month and compare with people not infected as control. (100) samples of venous blood were collected randomly during the period from November 23, 2021 to March 23, 2022, and the result was 63 infections (40 male, 23 . female) and 37 not infected (20 male,17female). The number of people who recovered a month after infection was 63 (40 males and 23 females). The results of the study related to the phagocytic activity of cells were reached Polynuclear, with high significant differences at (P